(untitled) (Journal of the College of Basic Education, 2022)
The present study aims at knowing the effect of educational drama in the acquisition of the students of the students of fifth grade in literary branch in the subject of Literature and Texts. The researcher put the following zero hypothesis: “there is no statistically significance differences at the at the level of (0.05) between the average score of the experimental group who were study the subject of Literature and Texts according to the use educational drama and the average score of the control group who were taught the subject according to normal methods”. The researcher chooses purposely the school of hind for Girls which include two sections, and chose randomly section (A) to represent the control group, while section (B) represents the experimental group. The total sample attained (50) students as (25) per each group students per each section. The researcher matched the two groups in the (age, marks in final exam of the previous year in Arabic, lingual ability text, use of Chi-Square). After determine the themes of the scientific material which is taught by the researcher herself, she exposed them to group of experts and judges, in the light of their opinions the required amendments are made. The plans become ready for application. The researcher prepared an acquisition test made up of (30) items the type of multiple choice on group of experts to verify the validity of the test. The sample included (150) students from Omar Al-Mokhtar School for Girls. After analyzing the students answers by the use of the statistical means he found that all the items are valid, and Kudor-Richardson. Constancy attained (0.80) which is good. After the end of experiment which lasted for five weeks the data obtained were analyzed by the use of the suitable statistical means, it was found that there is no statistically significance differences at the at the level of (0.05) between the average score of the experimental and control group for the experimental group who were study the subject of Literature and Texts according to the use educational drama. According to the results, the researcher conclude that educational drama is more effective than the normal methods it leads to the activation of the etching process and to positive results that effects the educational level for the students of fifth grade in literary branch in the subject of Literature and Texts. According to the results of study, the researcher concludes that educational drama is more effective that the normal method and leads to the activation of educational level for the students of fifth grade in literary branch in the subject of Literature and Texts. He recommends the necessity of using the educational drama as a means in teaching to simplify the concepts. He suggests making similar study in other branches of Arabic. Making a similar study in order to know the effect of educational drama educational drama in other variables like the acquisition and retain of information other branches of Arabic. Making a similar study in order to know the effect of educational drama educational drama on the improvement of educational level for the students other branches of Arabic: listening, conversation and writing.